A computer simulation of the effect of dusty particles on the characteristic of RF discharges - Kravchenko, O.Yu.; Vakulenko, A.V.; Lisitchenko, T.E.; Levada, G.I.; Yastrub, Yu.A. (Вопросы атомной науки и техники, 2007)
We are carried out the computer simulation of the dust cloud dynamics in the radio frequency (RF) discharges at the microgravity conditions using PIC/MCC method for electrons and ions and hydrodynamics model for dust particles. The moving of dust particles is governed by the electrostatic force, ion and neutral drag forces, which are averaged over period of RF discharge. The obtained results show that dust particles form layer with sharp boundaries in the discharge chamber. Locations of the layer boundaries don't coincide with the edges of the rf-sheathes and depend on size of dust particles and ion density in discharge. Проводиться комп’ютерне моделювання динаміки пилового згустку в радіочастотних розрядах в умовах мікрогравітації. Використовується PIC/MCC метод моделювання для електронів та іонів, а також гідродинамічна модель для пилових частинок. Рух пилових частинок визначається електростатичною силою, силами тертя з іонами та нейтралами, які усереднюються по періоду радіочастотного розряду. Одержані результати показують, що пилові частинки формують шари з різкими границями в розрядній камері. Положення границь пилових шарів не співпадають з границями приелектродних шарів і залежать від розміру пилових частинок та іонної густини в розряді. Проводится компьютерное моделирование динамики пылевого сгустка в радиочастотных разрядах в условиях микрогравитации. Используется PIC/MCC метод моделирования для электронов и ионов, а также гидродинамическая модель для пылевых частиц. Движение пылевых частиц определяется электростатической силой, силами трения с ионами и нейтралами, которые усредняются по периоду радиочастотного разряда. Полученные результаты показывают, что пылевые частицы формируют слои с резкими границами в разрядной камере. Положения границ пылевых слоев не совпадают с границами приэлектродных слоев и зависят от размера пылевых частиц и плотности ионов в разряде.